2012
DOI: 10.7598/cst2012.102
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Determination of Titanium(IV) by Using 3,4-Dihydroxybenzaldehydeisonicotinoyl- hydrazone(3,4-DHBINH) as a Chromogenic Agent

Abstract: 3,4-Dihydroxybenzaldehydeisonicotinoylhydrazone(3,4-DHBINH) was prepared, characterized with spectral analyses and used for developing a new method for the simple, sensitive and rapid spectrophotometric determination of titanium(IV) which gives maximum absorbance at wave length 370 nm. The metal ion gives a yellow colored complex with 3,4-DHBINH in acetate buffer of pH 3.5 with 1:2 (metal: ligand) composition. The method obeys Beer's law in the range 0.5-4.25 ppm of titanium(IV). The molar absorptivity and San… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…A reversed-phase liquid chromatographic method for the determination of titanium with 5,5'-methylenedisalicylohydroxamic acid (MEDSHA) has been described by Bagur et al [5]. Separation and determination of titanium (IV) at trace levels in different matrices including industrial wastewater have been reported employing solid phase extraction (SPE) [6][7][8][9][10][11]. SPE has several advantages e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reversed-phase liquid chromatographic method for the determination of titanium with 5,5'-methylenedisalicylohydroxamic acid (MEDSHA) has been described by Bagur et al [5]. Separation and determination of titanium (IV) at trace levels in different matrices including industrial wastewater have been reported employing solid phase extraction (SPE) [6][7][8][9][10][11]. SPE has several advantages e.g.…”
Section: Introductionmentioning
confidence: 99%
“…SPE has several advantages e.g. simple operation, low cost, no time consuming, good selectivity, higher preconcentration factor, rapid phase separation and the ability to be combined with different modern analytical techniques [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%